State of the people Residing inside Similipal Forest, Odisha, India - Swain, Debabrata (Indian Forester, 2022)
Similipal forest is situated in Mayurbhanj district of Odisha, India. It is both a tiger reserve and a biosphere reserve notified in 1973 and 1994 respectively by Government of India. The tribes residing in the district of Mayurbhanj are Bathudi, Bhumija, Kharia, Kolha, Mankidia, Munda, Santal, Bindhani and others. There are 62 villages inside Similipal (four in the core and 58 in the buffer zone of the reserve) and about 1200 villages located in the transitional zone. The people in and around Similipal lead a subsistence living. The study reveals that there is extreme poverty, unavailability of schools and remoteness of tribal habitations in the core area. But there is an increase in per capita income and a decent living for the families of relocated community. Simultaneously, wild animals found extensive inviolate area for movement and reproduction in the core area of Similipal reserve from where human habitation is relocated.